Application of the C3-binding motif of streptococcal pyrogenic exotoxin B to protect mice from invasive group a streptococcal infection. - Chih-Feng Kuo; Nina Tsao; Miao-Hui Cheng; Hsiu-Chen Yang; Yu-Chieh Wang; Ying-Pin Chen; Kai-Jen Lin (PLoS ONE)
Group A streptococcus (GAS) is an important human pathogen that produces several extracellular exotoxins to facilitate invasion and infection. Streptococcal pyrogenic exotoxin B (SPE B) has been demonstrated to be an important virulence factor of GAS. Our previous studies indicate that SPE B cleaves complement 3 (C3) and inhibits the activation of complement pathways. In this study, we constructed and expressed recombinant fragments of SPE B to examine the C3-binding site of SPE B. Using enzyme-linked immunosorbent assays and pull-down assays, we found that the C-terminal domain, containing amino-acid residues 345-398, of SPE B was the major binding site of human serum C3. We further identified a major, Ala376-Pro398, and a minor C3-binding motif, Gly346-Gly360, that both mediated the binding of C3 complement. Immunization with the C3-binding motifs protected mice against challenge with a lethal dose of non-invasive M49 strain GAS but not invasive M1 strains. To achieve higher efficiency against invasive M1 GAS infection, a combination of synthetic peptides derived from C-terminal epitope of streptolysin S (SLSpp) and from the major C3-binding motif of SPE B (PP6, Ala376-Pro398) was used to elicit specific immune response to those two important streptococcal exotoxins. Death rates and the severity of skin lesions decreased significantly in PP6/SLSpp-immunized mice that were infected with invasive M1 strains of GAS. These results indicate a combination of the C3-binding motif of SPE B and the protective epitope of SLS could be used as a subunit vaccine against invasive M1 strains group A streptococcal infection.